Lock, stock and two smoking barrels [videorecording (DVD)] - Ritchie, Guy; Moran, Nick, 1969-; Flemyng, Jason; Fletcher, Dexter, 1966-; Statham, Jason, 1967-; Mackintosh, Steven; Jones, Vinnie, 1965-; Sting (Musician) (Focus Features, 2006)
A streetwise charmer who loses his friends' money in a rigged game comes up with a plan to make everything come out right, but ends up in a comedy of errors.